(untitled) (Revista de Ciências Agroveterinárias, 2021)
The objective of this work was to evaluate the effects of clonal rootstocks and self-rooted plants on the physicochemical quality of ’Letícia’ plums in the mid-west of Santa Catarina. The evaluated fruits were from the 2018 to 2020 crops, from an experimental orchard of cv. Letícia, whose plants were grafted onto 19 different accessions (cultivars, interspecific hybrids, and selections) used as clonal rootstocks, in addition to own-rooted Letícia, at the Epagri Experimental Station in Videira-SC. Here, we evaluated total acidity, soluble solids content, ratio, pH, flesh firmness, and epidermis color of the fruits. The pH values ranged from 2.98 for the ’Barrier’ rootstock (2018) to 3.68 for plants on ’Santa Rosa’ (2020). ‘Santa Rosa’ as rootstock stood out for the highest ratio (19.46) in the 2020 harvest, followed by ‘Flordaguard in 2018 (14.92). The highest firmness values were obtained for GxN9 in 2018 and Nemared in 2020, and the lowest for ’Santa Rosa’ in 2019 and 2020. The performance of the rootstocks was not repeated throughout the evaluated crops, demonstrating that the yield factor had a greater influence on fruit quality, except for ’Santa Rosa’. The fruits of plants grafted onto ’Santa Rosa’ showed more advanced maturation at harvest. ’Letícia’ plums produced on ’Santa Rosa’ presented precocity of maturation in relation to the other tested clonal rootstocks. The rootstocks Rigitano, Clone 15 (Prunus mume), Nemared and I-67-52-4 (P. persica) showed incompatibility with the ’Letícia’ canopy cultivar. Own-rooted ’Leticia’ plants produce fruits with physicochemical characteristics similar to those produced on plants grafted on the tested rootstocks, indicating that the own-root cultivation is a technically interesting option for this cultivar.